Contribuições da práxis histórica de Paulo Freire às pesquisas e propostas sobre educação contínua de educadores(as) - Paula, Lucimara Cristina de (Universidade Federal de São Carlos, 2011)
Various authors have denounced the inadequacy of the proposals for continuing education offered to teachers of early elementary, by the distance they keep, in their school curriculum, of school s reality, and the inability to contribute to the establishment of a significant professional and institutional transformation in education, which points out the importance of reflecting and refocusing the proposals of the formation of trainers. Assuming that only a democratically, critical and politically committed formation, with a humanised education of children, youth and adults can contribute to the transformation of individuals and their contexts, the research is rooted on the philosophical and pedagogical principles of educator Paulo Freire. According to these principles, humans are in the world, with the world and with each other, conditioned by time and space in which they live. Therefore, trainers of teachers form and will be forming in their relationships, conditioned by the historical, social, political, cultural and economical system that they make and that influences them. Considering the impact that such system and educational policies exert on the working and behaviour of the teaching professionals, as well as on the functioning of educational institutions, we present the following question: how has the formation of trainers of teachers of early elementary, which act or have acted in continuing education programs, been handled by the Department of Education of the State of São Paulo, and how to reorient the proposals of such programmes within the framework of research and training, from the trajectory of life and occupation of the trainers, through the assumptions of Progressive Pedagogy of Paulo Freire? In order to answer this question, we selected two procedures: the first enabled the wider analysis of the complex processes of formation and auto formation experienced by the trainers, in the course of their personal and professional paths interviews to collect their life stories; the second allowed to identify and analyse the ideas and positions of these people on the relevant themes related to life in the profession, from the freirean frame and the Communicative Critical Methodology - dialogues between each participant and the researcher. Data collection and data analysis are performed from the recording and transcript of conversations with two educators who work continuously with the training of teachers: one that participates in policy making training effected by the Department of Education of the State of São Paulo, and another who works in the implementation of such policies, within the framework of the boards of education. The base of all the research and, most importantly, the results of the dialogues with participants, confirm that the trainers consist of the subjectsubject, subject-object and subject-object-subject relations. These relations establish the historical conditions of living, schooling, social classes, which provide them with learning, thoughts and with the confrontation of situations that affect and oppress, accommodate or rupture, cause barriers or satisfactions, through the constant dialectical movement of doing and redoing, making and remaking. We verify the potenciality of the historical freirean Praxis to the indication of some principles and actions focused on research and proposals for continuing education of (the) educators, in the sphere of schools, public education, universities and trade unions, involving the unity in diversity, the criticality and the dialogue present in the work of Freire and the methodology adopted.
Keywords: Professores - formação; Formação continuada de professores; Freire, Paulo Reglus Neves, 1921-1997; Histórias de vida; Educação contínua de educadores(as); Formadores(as) de professores(as); Paulo Freire; Continuing education for educators; Trainers of teachers; Life stories; CIENCIAS HUMANAS::EDUCACAO